1996
DOI: 10.1136/gut.38.4.619
|View full text |Cite
|
Sign up to set email alerts
|

Colitis complicating chronic granulomatous disease. A clinicopathological case report.

Abstract: Background-This report concerns a female patient now aged 24 years, diagnosed at the age of 7 years as suffering from chronic granulomatous disease. At age 20 she developed diarrhoea accompanied by rectal bleeding. Endoscopy showed extensive colitis. She failed to respond to medical treatment and underwent total colectomy two years later. Aims-To discuss the histological changes in the colon in chronic granulomatous disease.Results-There was extensive mucosal inflammation throughout colon and rectum resembling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Colitis is a major manifestation and complication of CGD, with at least 50% of patients developing symptomatic bowel disease, including anal fissures, perirectal abscesses, fistulae, bowel obstruction, cramping, and diarrhea [5,[30][31][32][33]. The consequences of this include iron deficiency, growth retardation, fatigue, and discomfort.…”
Section: Discussionmentioning
confidence: 98%
“…Colitis is a major manifestation and complication of CGD, with at least 50% of patients developing symptomatic bowel disease, including anal fissures, perirectal abscesses, fistulae, bowel obstruction, cramping, and diarrhea [5,[30][31][32][33]. The consequences of this include iron deficiency, growth retardation, fatigue, and discomfort.…”
Section: Discussionmentioning
confidence: 98%
“…Occasionally colitis has been reported 2-4. It has been suggested that the colitis may be an unusual association,4 5 or that it might be caused by infection,3 6 or that it is a manifestation of CGD 5-7. In a recent literature review of gastrointestinal (GI) manifestations in CGD, it was estimated that 50% of patients had intestinal obstruction or anal fissure and diarrhoea.…”
mentioning
confidence: 99%
“…12,15 Even rarer is the description of these colitides resembling UC, because colitis in CGD is usually described as Crohn-like. [7][8][9][10] The case we describe here (the second reported to date) is unusual, in that it occurred in an adult, and had histologic features resembling those of UC.…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting that similar rare cases needed total colectomy. 11,12 The patient continues to date, after more than 5 years, to have a good quality of life concerning his colitis, maintained in remission through twice-a-week mesalazine enemas and decontamination through distal ileostomy. Thus, we feel that by averting the continuous flow of pathogens within the colon, this may have had the opportunity to heal and to maintain the healing process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation